Analisis Literasi Matematika Siswa SMP Dalam Menyelesaikan Soal Model AKM Pada Konten Geometri - Fitria Hairunnisa; Mariyanti Elvi; Metta Liana (Universitas PGRI Adi Buana Surabaya, 2023)
SMP Negeri 10 Tanjungpinang has varied mathematical literacy because learning at school still sees students' abilities due to the impact of Covid-19. Students are facilitated with questions in the form of AKM but students tend to understand the questions less because of the long narrative. This study describes students' mathematical literacy in solving Minimum Competency Assessment (AKM) model questions on geometry content. The approach used in this is qualitative with descriptive method. The research subjects were 3 students consisting of high, medium, and low categories. Data collection techniques in the form of tests and interviews. Data analysis techniques used data reduction, data presentation, and conclusion drawing. Researchers ensured the validity of the data, using triangulation techniques by equalizing the results of tests and interviews. The result of this study is the classification of students' mathematical literacy based on categories. Students in the high category have good literacy where they are able to fulfill all three indicators, namely formulating problems, applying concepts, and interpreting solution results. While students in the medium category are able to fulfill both indicators, namely formulating problems and applying concepts and have not fulfilled the indicator of interpreting the results of the solution. Low category students were only able to fulfill the indicator of formulating problems and did not fulfill the indicators of applying concepts and interpreting the results of the solution.